PENYUSUNAN PROGRAM SUPERVISI PENDIDIKAN PADA MADRASAH KABUPATEN NAGAN RAYA - Junias Zulfahmi (Jurnal Ilmiah Peuradeun, 2014)
Supervisors play an important role in improving the quality of education in madrasah through coaching, academic supervision and managerial supervision. It is very tied to the performance of supervisors in the preparation of educational supervision programs should be relevant to the circumstances and needs of madrasah personnel. The issue that arises that the supervisor can not perform effective and efficient supervision due to the preparation of educational supervision programs do not fit the needs of personnel in the realization of the program so that the madrasah education supervision are not efficient. This study aims to investigate the performance of supervisors in the preparation of the Madrasah education program supervision Nagan Raya district. This study used a qualitative approach with descriptive analytical method. The results showed that the preparation of the Madrasah education program supervision Nagan Raya district based guidelines as a reference in the preparation of educational supervision programs. Steps taken in the preparation of educational supervision program based on the needs of the results of the previous year's program. The scope of supervision of education programs in the form of an annual program, the semester program, plan academic supervisory, managerial and supervisory plan.